Penilaian Keamanan Informasi Di Rumah Sakit Panti Wilasa Citarum Berdasar Indeks KAMI 5.0 - Kurniadi, Arif; Reandra Permana, Alpha; Wardoyo, Agung (Jurnal Informatika UPGRIS, 2026)
Regulation Number 24 of 2022 by the Minister of Health of the Republic of Indonesia addresses Data Security and Protection. The Panti Wilasa Citarum Hospital follows Hospital Accreditation Commision quality standards, particularly regarding MRMIK 13 which covers information technology regulations. The hospital assesses its information security readiness using the KAMI Index from BSSN, aligned with ISO/IEC 27001 standards, to evaluate the level of information security as it implements Electronic Medical Records.  The study involved a questionnaire from four respondents and interviews with the IT head. Results showed the following scores: electronic system category received 20 points (High), Governance 41 points (Maturity Level I plus), Risk Management 35 points (Level II), Information Security Framework 61 points (Level I plus), Asset Management 176 points (Level II), Information Security Technology 131 points (Level II), Personal Data Protection 60 points (Level II), and Third Party Security at 53%. The overall score was 504 points, reflecting a "Basic Framework Compliance" at Maturity Level II, which did not meet KAMI Index requirements. The hospital must enhance information security through training, awareness, and periodic assessments.